(3TQM GdgOGjIs - (3GdMSjfj GdnerjnHPj, bGVj ejQ, MSjf Hf eYjf GdOjf, J (B910 (3g`s
(3ChdgG (B:s
.. (3GYde Cf GdMceI Yde HCMhGd CYjGf GdehLhOGJ Ydi eG gj Ydjg aj faS GdCeQ HbOQ GdWGbI GdHTQjI hJdc GdCYjGf EeG GdCaYGd hGdCYeGd GdJj hLhOfG HbOQJfG hGNJjGQfG aGdYGde HCMhGd GdChd (B...s
(3BNQgG (B:s
.. (3HCf GdfahS GdcGedI JeKd ajQO GdeYbhdGJ ajgG Ydi eG gj Ydjg (B.. (3COQc abW aUGQJ eY Pdc PhGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\260s
(3GdPQjYI (B14\2053s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s